Attentional focus strategies used by regular exercisers and their relationship with perceived exertion, enjoyment, and satisfaction - Emad, M.; Neumann, D. L.; Abel. L. (Journal of Human Sport & Exercise, 2017)
Individuals can focus their attention in different ways during exercise and different foci may influence psychological states experienced. The present study examined the distribution of attentional focus strategies in exercisers and their relationships with gender, perceived exertion, enjoyment, and satisfaction. Regular exercisers (176 females, 144 males) completed a measure of attentional focus and rated their perceived exertion, enjoyment, and satisfaction during an exercise session. All participants used more than one type of attentional focus during an exercise session. Males spent more time than females attending to task-relevant thoughts and external cues whereas females spent more time attending to task-irrelevant thoughts and external distractions. In females and males, time spent engaging in task-irrelevant thoughts was negatively correlated with perceived exertion and satisfaction with exercise. For females only, time using external distractions was negatively correlated with satisfaction and positively correlated with enjoyment. For males only, time attending to task-relevant external cues was positively correlated with perceived exertion and enjoyment. The observed gender differences in attentional focus preferences and the relationships with psychological states have implications for advice given to exercisers and approaches that aim to promote adherence to exercise programs.